Incidence of Post-Operative Pain and Vomiting after Elective Laparoscopic Cholecystectomy with Per-Operative High Versus Low Intra-Abdominal Pressure of Carbon Dioxide (CO2) - Muhammad Azhar, Sadia, Syed Arif Hussain, Masab Niaz, Tallal Ghazanfar, Usman Ahmad (Pakistan Journal of Medical & Health Sciences, 2024)
Background: Laparoscopic cholecystectomy is performed by creating pneumoperitoneum via carbon dioxide pressure between 9-14 mmHg. Increased incidence of pain, vomiting and nausea has been related with higher pressures of carbon dioxide pressures leading to significant morbidity and increased length of stay in hospital. Objective: To assess the incidence of post-operative pain and vomiting after elective laparoscopic cholecystectomy with per operative high versus low intra-abdominal pressure of carbon dioxide. Study design: Comparative analytical study Place and duration of study: Department of Surgery, Muhammad Aslam Chaudary Hospital, Wah Cantt from 1st January 2023 to 30th June 2023. Methodology: One hundred and ten patients were recruited within the age group of 18-55 years undergoing elective laparoscopic cholecystectomy for symptomatic gall stones. The patients were divided into two groups with each group having 55 patients in it. Group I was administered with low gas pressure of carbon dioxide during the surgery while in group II a high-pressure carbon dioxide was administered. Post-operative pain, nausea and vomiting was recorded at various intervals. Length os stay in hospital was also recorded in both the groups. All the results were compared within group I and group II. Pain maintenance was ensured. The vomiting symptoms were monitored at postoperative 24 hours up till five times. The patient’s nausea and vomiting were recorded at various intervals such as at 0-4, 4-8, 8-12, 12-24 hours as post operative through Visual analogue scale (VAS) and assessment of vomiting was performed through episodic estimation per 24 hours. Results: The Group II patients have relatively more weight than Group I. There were significantly more females than males in this study (p<0.05). The duration of anaesthesia, surgery and pneumoperitoneum in minutes was noticed lower in Group II than Group I patients. The difference between pain complaints was significantly reduced with 18.1% at recovery in group I and 10.9% after 4 hours. In group II 43.63% of cases had pain at time of recovery and 32.72% had it after 4 hours of recovery. The present study results showed that there were a greater number of cases reported between 0-4 hours in high carbon dioxide group II than low carbon dioxide Group I. Similar trend was noticed in the 4-8, 8-12 and 12-24 hours. The difference in nausea cases in low and high gas pressure groups presented an insignificant variance with an increased trend of nausea observed in high carbon dioxide group II than group I. Conclusion: The shoulder pain was reduced at an incidence of 21.82% in low pressure of carbon dioxide in comparison with high pressure however there was no change or reduction in nausea and vomiting observed in low pressure group I than group II cases. Keywords: Incidence, Post-operative pain, Vomiting, Elective laparoscopic cholecystectomy, Intra-abdominal pressure